2019
DOI: 10.1136/bmj.l5167
|View full text |Cite
|
Sign up to set email alerts
|

US opioid prescribing: the federal government advisers with recent ties to big pharma

Abstract: With the US facing an epidemic of opioid deaths linked to overprescribing, Tim Schwab finds that the influential National Academies of Science, Engineering and Medicine has not disclosed that one of its presidents, and members of a panel it convened to advise on prescribing opioids, had recent links to the drug industry

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…One of the main factors leading to regulatory capture in public health is the conflicts of interest of officials who serve simultaneously as researchers and consultants on behalf of pharmaceutical companies (DeLong, 2012;Rogers, 2019). It seems that the prevalence and the magnitude of such conflicts of interest (COls) have only increased over the years (Bekelman et al, 2003;Boyd et al, 2003;Gøtzsche, 2013;Schwab, 2019).…”
Section: Retraction Of Papers On Vaccinesmentioning
confidence: 99%
“…One of the main factors leading to regulatory capture in public health is the conflicts of interest of officials who serve simultaneously as researchers and consultants on behalf of pharmaceutical companies (DeLong, 2012;Rogers, 2019). It seems that the prevalence and the magnitude of such conflicts of interest (COls) have only increased over the years (Bekelman et al, 2003;Boyd et al, 2003;Gøtzsche, 2013;Schwab, 2019).…”
Section: Retraction Of Papers On Vaccinesmentioning
confidence: 99%
“…A recent article in the BMJ expressed concern that the National Academies of Science, Engineering, and Medicine (NASEM)—an NGO established by federal statute with the express purpose of providing independent advice to the federal government in the United States—had received millions of dollars from several pharmaceutical companies (including opioid manufacturers), as well as gifts from members of the Sackler family (Schwab 2019 ). The article also expressed concern that members of NASEM panels, including one commissioned to advise policymakers on clinical practice guidelines for prescribing opioids, had received payments from opioid companies (in the form of research funding, consultancy fees, and advisory board retainers).…”
Section: Influencing Patient Advocacy Organizations Professional Socmentioning
confidence: 99%
“…In the Lancet, an editorial describes the updated American College of Physicians COI procedure during clinical guideline development, with a continuous disclosure policy and severity grading of COIs with corresponding mitigating actions taken. 2 The BMJ reported that an advisory body on opioid policies for the US Food and Drug Administration did not publicly disclose that one of its presidents (and a number of panel members) had recent industry links, 3 although it should be noted that said advisory body 4 and president 5 have responded.…”
Section: Lettersmentioning
confidence: 99%